Makna Sekaf dan Tsiom Manikin dalam Tradisi Perkawinan Suku Ketmoen di Desa Kuluan Kecamatan Biboki Feutleu Kabupaten Timor Tengah Utara - Nataliani Ketmoen; Antonius Bere; Clotilde Seran; Yuditha Sofiana Kofi; Augusta D.J.Magalhaes (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2024)
Sekaf and Tsiom Manikin in wedding traditions Ketmoen tribe in Kuluan Village, Biboki Feotleu District, North Central Timor Regency. The problem in this research is what the process and stages of implementing the Sekaf and Tsiom Manikin are in the marriage traditions of the Ketmoen Tribe in Kuluan village, Biboki Feotleu District, what is the meaning of Sekaf and Tsiom Manikin in the traditional marriage traditions of the Ketmoen Tribe in Kuluan village, Biboki Feotleu District. This research uses a qualitative descriptive method. The data collected is both primary data and secondary data that has been obtained from the field. Data collection techniques were carried out using observation, interviews and documentation. The subjects in this research were village heads and tribal heads. This research shows that the traditional marriage process in Kuluan village generally has the same process and stages, but is then divided into rules regarding the size of the dowry according to the statutes/ART in each tribe. The process and stages in the marriage tradition consist of four stages, namely: (a). tois tua (get to know), (b). onaf hauno'o (proposing marriage), (c) puah manus (lifting the first Belis), (d) tsiom manikin (accepting blessings). The meaning of Sekaf itself is as a substitute, in this case taking the place of her mother who has gone to follow her husband's family, while Tsiom Manikin has the meaning of receiving a traditional blessing from the woman's tribal house as a blessing to go and follow her husband.